Feedlot and pasture fattening tests with feeder lambs. Studies carried on by the Department of Animal Husbandry and the Garden City Branch Experiment Station. - Bell, T.D.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
The tests this year compared whole milo with ground milo grain fed with a standard roughage ration of ground sorghum stover, protein supplement, and supplemental salt and limestone. The roughage comparisons included (1) all sorghum stover, (2) sorghum stover and alfalfa hay, and (3) beet top silage and alfalfa hay. One lot of lambs received the sorghum stover-alfalfa hay-milo grain ration as pellets. One lot on the standard ration received 6 milligram pellet implants of stilbestrol at the beginning of the feeding period; another lot on the standard ration received estradiol-progesterone (Synovex) pellet implants at the start of the tests; and another lot of lambs was given 2 milligrams of stilbestrol daily in the standard ration. Two lots of lambs were run on irrigated milo pasture with supplemental alfalfa hay during the early part of the grazing period. Additional grain was provided after approximately 60 days, and one lot was brought into the dry lot for finishing after 63 days on pasture. Another lot of lambs was grazed on irrigated wheat pasture for 63 days and brought in (because of snow) to be finished in the dry lot.
Keywords: Sheep; Milo; Beet top silage; Synovex; Gain